Characteristics of Speech in Finding a Match Through the TikTok App - Afrinda, Putri Dian; Bahardur, Iswadi (Bhandar: Harvesting Community Service in Asia, 2024)
Avoid devoting too much space for introduction or background, which is unnecessary. Various phenomena of popular culture today have become an inseparable part of the dynamics of societal development. Various applications are also created as products of popular culture. Current applications reflect the culture that is widely used or popular. Popular culture is the culture that is liked by many people and can be easily found on social media such as Facebook, Instagram, and TikTok. This research uses qualitative methodology as a research procedure that produces descriptive data in the form of written or spoken words from people and observed behaviors. Characteristics can be identified from the storytelling strategies used. The digital discourse used by someone generally employs commissive speech acts such as giving challenges, proposing, and offering with strategies that mark group identity, as well as amplifying attention, approval, and sympathy. The phenomenon that supports the rise of popular culture on contemporary applications allows users to freely express themselves. TikTok users engage in conversation to create attraction, making the opposite sex more interested. From the types of speech acts and communication strategies used, the characteristics of digital speech employed in contemporary applications can be identified. This research provides deeper insights into how digital technology is changing communication patterns in the context of matchmaking and offers a new perspective in the study of digital linguistics and interpersonal communication. This research also shows the shifting Eastern cultural values between men and women. It is hoped that the findings from this research can contribute to the development of more effective matchmaking applications, as well as enrich the understanding of the impact of technology on human interactions.